PENGABDIAN MASYARAKAT MELALUI EDUKASI RUMAH SEHAT PADA SISWA SMKN 12 GARUT - Yosita, Lucy (Lentera Karya Edukasi, 2023)
The comfortable housing and environment condition is the priority nowadays. All of daily activities can be reach if the condition of housing and environment is well. The young generation is the community in which their behaviour still much more have flexibility to develop their habit as well as their skill to reach sustainable environment and sustainable community. Therefore its is necessary to plan and to apply many training for the young generation. Garut city is on of the city which have the good potential of nature as well as tourism. The sustainable environment is one of important factor for sustainable tourism in Garut, therefore it is necessary to develop the habit or behaviour of the community by sustainable program. SMKN 12 Garut as the location of this community empowerment-program in which to be selected as location of this training is have several program, there are: 1). Program of Multimedia  (2). Program of Agribussines of Crop and Holtikultur, (2). Technical and Bussines of Motorcycle, (4). Islamic Banking and (5). Online Bussines and Marketing. Education Traning of Healthy Home is very necessary to keep the psychological quality of the students as well as theory family, therefore by this the continuity of activity of community can be reach. By this training which is holding by the team of lecturer is can be assessed succeed enough, the students were very interisting by this training because they got refreshing material by this friendly and fun-training.